Randomised controlled trial of the short-term effects of OROS-methylphenidate on ADHD symptoms and behavioural outcomes in young male prisoners with attention-deficit/hyperactivity disorder (CIAO-II) - Philip Asherson; Lena Johansson; Rachel Holland; Tom Fahy; Andrew Forester; Sheila Howitt; Stephen Lawrie; John Strang; Susan Young; Sabine Landau; Lindsay Thomson (Trials, 2019)
Abstract Background Attention-deficit/hyperactivity disorder (ADHD) is a highly prevalent disorder, seen in 20–30% of young adult prisoners. Pharmacoepidemiological studies, a small randomised controlled trial and open trial data of methylphenidate suggest clinically significant reductions in ADHD symptoms, emotional dysregulation, disruptive behaviour and increased engagement with educational activities. Yet, routine treatment of ADHD in offenders is not yet established clinical practice. There is continued uncertainty about the clinical response to methylphenidate (MPH), a first-line treatment for ADHD, in offenders, who often present with an array of complex mental health problems that may be better explained by states of inattentive, overactive, restless and impulsive behaviours. To address this problem, we will conduct an efficacy trial to establish the short-term effects of osmotic-controlled release oral delivery system (OROS)-methylphenidate (Concerta XL), an extended release formulation of MPH, on ADHD symptoms, emotional dysregulation and behaviour. Methods This study is a parallel-arm, randomised, placebo-controlled trial of OROS-MPH on ADHD symptoms, behaviour and functional outcomes in young male prisoners aged 16–25, meeting Diagnostic and Statistical Manual of Mental Disorders, fifth edition criteria for ADHD. Participants are randomised to 8 weeks of treatment with OROS-MPH or placebo, titrated over 5 weeks to balance ADHD symptom improvement against side effects. Two hundred participants will be recruited with a 1:1 ratio of drug to placebo. The primary outcome is change in level of ADHD symptoms after 8 weeks of trial medication. Discussion Potential benefits include improvement in ADHD symptoms, emotional dysregulation, attitudes towards violence and critical incidents and increased engagement with educational and rehabilitation programmes. Demonstrating the efficacy and safety of MPH on ADHD symptoms and associated impairments may provide the data needed to develop effective healthcare pathways for a significant group of young offenders. Establishing efficacy of MPH in this population will provide the foundation needed to establish long-term effectiveness studies with the potential for demonstrating significant reductions in criminal behaviour and improved health-economic outcomes. Trial registration ISRCTN registry, ISRCTN16827947, 31st May 2016; EudraCT number, 2015-004271-78, 31st May 2016. Last particpant last visit 6 June 2019. Data lock 27 August 2019.